2021
DOI: 10.3390/agronomy11071326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clay, Soil Organic Matter, and Soil pH on Initial and Residual Weed Control with Flumioxazin

Abstract: Greenhouse studies were conducted to evaluate the effects of soil organic matter content and soil pH on initial and residual weed control with flumioxazin by planting selected weed species in various lab-made and field soils. Initial control was determined by planting weed seeds into various lab-made and field soils treated with flumioxazin (71 g ha−1). Seeds of Echinochloa crus-galli (barnyard grass), Setaria faberi (giant foxtail), Amaranthus retroflexus (redroot pigweed), and Abutilon theophrasti (velvetlea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…Sorption-desorption studies showed that the sorption capacity of flumioxazin in soil correlates positively with increasing CEC and OM of the soil. The correlation coefficients between sorption K d values and CEC and OM content were 0.9909 and 0.8390, respectively [36]. These data are consistent with the present study, where the higher OM and CEC content of Ultisol compared to Oxisol resulted in higher doses to achieve C 80 and GR 80 .…”
Section: Flumioxazinsupporting
confidence: 91%
See 1 more Smart Citation
“…Sorption-desorption studies showed that the sorption capacity of flumioxazin in soil correlates positively with increasing CEC and OM of the soil. The correlation coefficients between sorption K d values and CEC and OM content were 0.9909 and 0.8390, respectively [36]. These data are consistent with the present study, where the higher OM and CEC content of Ultisol compared to Oxisol resulted in higher doses to achieve C 80 and GR 80 .…”
Section: Flumioxazinsupporting
confidence: 91%
“…The sorption of flumioxazin to soil particles is mainly attributed to the hydrophobic binding. OM and clays provide the necessary conditions for the sorption of flumioxazin due to the hydrophobicity of the particles [36]. However, the bioavailability of flumioxazin in soil solution also depends on the water content of the soil.…”
Section: Flumioxazinmentioning
confidence: 99%
“…A generalized linear mixed model with a beta distribution and logit family ( glmmTMB package; Brooks et al 2017) was used to analyze both response variables. PRE herbicide efficacy is known to vary by year and location because of weather and soil conditions (Glaspie et al 2021; Landau et al 2021a) and soil seedbank weed community composition (Striegel et al 2021a). Therefore, data were analyzed separately by weed species and site-year.…”
Section: Methodsmentioning
confidence: 99%
“…Soil properties should also be considered when selecting the proper herbicide as part of a well-designed crop rotation. For example, flumioxazin persistence in soil is highly dependent on organic matter and water content, which are directly involved in the microbial-mediated degradation of this herbicide (Chen et al 2021;Glaspie et al 2021). In addition, soil texture plays a major role in herbicides' sorption on soil particles and their bioavailability.…”
Section: Practical Considerations For Imazapic and Flumioxazin Use In...mentioning
confidence: 99%